PENGARUH BAHAN AJAR POWERPOINT BERBASIS 3D TERHADAP PENINGKATAN MINAT BELAJAR MAHASISWA - Farman, Indra; Yusniati; Ade Marela (TEKNOS: Jurnal Pendidikan dan Teknologi, 2023)
The development of the times is increasing every year so that it requires educators to be able to use the latest technology. The existence of the Covid-19 pandemic requires that the learning system be implemented in a hybrid manner, but the constraints of using ordinary teaching media cannot improve the quality of learning. This research aims to find out whether teaching media 3D-based can significantly increase students' interest in learning. This research uses an experimental method using One Group retest-Posttest. the results of the study showed that there were differences in the level of knowledge before and after being given treatment. shows that the use of PPT 3D which has been implemented in the Information Technology Study Program class gets a positive response from students, has an influence on student learning outcomes and is proven to be more effectively used in learning. The effect on learning outcomes has been proven by increasing the value of student learning outcomes significantly. So it can be concluded that the results of research on the influence of 3D-based PowerPoint teaching materials on increasing student learning interest. results. Abstract should end with a comment about the importance of the results or conclusions brief.